Traditional Practice of Bapanteh in Marriage in Traditional Society of Kerinci Dictrict: Victor Turners Symbolic Analysis - Epriandi, Alzaki; Iskandar, Nuzul; Zufriani, Zufriani (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2025)
The Bapanteh tradition is a pre-wedding ritual practiced by the Hiang Village community in Sitinjau Laut District, Kerinci Regency. This tradition is not merely ceremonial, but reflects deep cultural values such as kinship, solidarity, and cultural preservation. This study seeks to investigate the symbolic meanings embedded in the Bapanteh tradition, explore the actual practices involved, and understand the reasons behind its preservation amidst modernization. Utilizing a qualitative research approach with Victor Turner’s symbolic analysis as the theoretical lens, data were collected through in-depth interviews with local elders, community members, and traditional leaders, as well as through participatory observation. Findings reveal that Bapanteh serves as a social mechanism to reinforce communal ties and express collective identity. It involves community cooperation in borrowing long batik cloths as symbolic offerings, which are then used to decorate the bride’s home, symbolizing interconnectedness among families. Although contemporary influences have led to adaptations such as reduced collective participation and the use of modern decorations, the symbolic essence of Bapanteh remains resilient. This study highlights the importance of preserving such traditions as they carry profound cultural meaning and serve as a unifying force in society. The findings contribute to a deeper understanding of the function of ritual and symbolism in maintaining cultural identity in an era of rapid social change.